A LncRNA panel within EpCAM-specific exosomes for noninvasive early diagnosing non-small cell lung cancer - Linyuan Liu; Danlei Li; Amei Zhuo; Jiachun Lu; Jianjun Zou; Guitian Huang; Zhaoting Hu; Zili Zhang; Yibin Deng; Lei Yang (Respiratory Research)
Abstract Background Plasma tumor-associated exosomes represent a promising source for cancer biomarkers; however, the role of long non-coding RNAs (lncRNAs) within these exosomes is not well-defined in non-small cell lung cancer (NSCLC). Methods We identified a panel of NSCLC-specific lncRNAs within plasma EpCAM-specific exosomes (Epexo) through a comparative analysis of lncRNA profiles between plasma Epexo and lung tissues. The panel’s diagnostic value was firstly evaluated in a retrospective cohort of 210 NSCLC patients and 245 healthy controls, and validated in a prospective cohort of 192 patients with pulmonary nodules (nodule size < 3 cm in diameter). The evaluation utilized the area under the ROC curve (AUC) based on a random forest model. For precision, repeat testing was conducted with 31 randomly selected samples. Additionally, 39 paired tissue-plasma samples were employed to assess the concordance of lncRNA expression between tissue and plasma within the same individuals. Results The panel, including linc01125, HNF1A-AS1, MIR100HG, linc01160, and ZNRF3-AS1, demonstrated superior capability in distinguishing early-stage NSCLC patients from controls, achieving AUC values of 0.805 and 0.856 in the discovery and validation set, respectively. The panel also showed potential for differentiating adenocarcinoma and squamous cell carcinoma. Repeat sample testing showed a consistency of 90.3% for this panel. The expression levels of MIR100HG and HNF1A-AS1 showed significant correlations between plasma Epexo and cancerous tissues. Conclusions The identified lncRNA panel, consisting of linc01125, HNF1A-AS1, MIR100HG, linc01160, and ZNRF3-AS1, presents a promising diagnostic tool for NSCLC. Clinical trial number not applicable.